Social Work in Ghana: Engaging Traditional Actors in Professional Practices (Journal of Comparative Social Work, 2011)
In contemporary Ghana, the traditional system and professional social work operate as two parallel systems within the field of social work. The aim of this study was to investigate if and how the teaching of contemporary professional social work in Ghana takes into account traditional actors and practices. The traditional system includes extended family members and traditional authorities such as chiefs or family heads. It formed the social institution that protected and cared for the vulnerable before (Western) social work was introduced as a formal profession in Ghana. A 10-week ethnographic field study was conducted at the Department of Social Work at the University of Ghana. The study employed a qualitative, social constructionist approach, interpreting the results within a theoretical framework of social world theory. The empirical material consisted of interviews with students and teachers, participant observation at lectures, and various documents. The main findings of the study were that professional social workers and traditional actors can be seen as members of two subworlds – the subworld of professional social workers and the subworld of traditional actors. Students and teachers discuss interventions from the perspective of social workers and traditional actors. Their ability to take different perspectives seems to be crucial for localisation – the process by which social work is made relevant to local culture and traditions. The interviewees’ accounts reveal how localisation is not only about culture, but also about social structures and practical considerations. The poor state of the social work profession in Ghana affects interventions in a profound way.